√x^p-q × √x^q-r × √x^r-p = 1
This answer telling guy I will mark as brainiest
Answers
Answered by
0
Answer:
Step-by-step explanation:
√x^p-q*√x^q-r*√x^r-p=1
proof
we know that, a^p × a^q = a^ (p+q)
so, ....
root x ^ (p-q+q-r+r-p) = 1
ins subtracting
(p-q+q-r+r-p) , we will get 1
as lhs = rhs
√x^p-q*√x^q-r*√x^r-p=1
THUS PROVED-----
Similar questions
Physics,
4 months ago
Political Science,
4 months ago
Math,
4 months ago
English,
8 months ago
Science,
8 months ago
Computer Science,
1 year ago
Chemistry,
1 year ago